Using connectivism theory and technology for knowledge creation in cross-cultural communication - Archana Shrivastava (Association for Learning Technology, 2018)
This study examined the significance of connectivism theory and technology for knowledge creation in cross-cultural communication. The findings rely on the exercise designed and conducted by the facilitators of two different institutions/universities based in two different countries. This exercise was conducted for two intercultural management classes in New Delhi, India and Graz, Austria. This article used student-centric teaching approach and output-oriented methodology based on the principles of connectivism and knowledge creation. It demonstrates how these approaches foster lifelong learning in students. The task involved selection of commercial advertisements (preferably national ones), in which students were expected to work in virtual teams and find cultural differences in the interpretation between the participants from two countries: India and Austria.The key findings of this article are the following: The students learnt that an answer to a specific question might match the expectations at one point of time with one specific group of people, but might be different in some other point or with some other group of people.They examined the role of connectivism and its potential application in knowledge creation.They learnt that people generally see the world not as it is, but as they are, or, as they are conditioned to see it.